Modelling the effect of energy consumption on different environmental indicators in the United States : The role of financial development and renewable energy innovations - Usman, Ojonugwa; Alola, Andrew Adewale; Ike, George N. (Wiley, 2021)
This study offers new insights into the relationship between energy consumption and environmental degradation in the United States by controlling for financial development, renewable energy innovations, economic expansion, and trade policy uncertainty over the period 1985:Q1 to 2014:Q4. Based on the flexible autoregressive distributed lag model, our findings show that energy consumption deteriorates the environment, while renewable energy innovations reduce CO2 emissions but has no significant effect on ecological footprint. Furthermore, the environmental Kuznets curve hypothesis is valid only when ecological footprint is used as an environmental indicator. The causality results establish a feedback effect between CO2 emissions and renewable energy innovations, a unidirectional causal flow from financial development to CO2 emissions, energy consumption, and economic growth. Also discovered is a unidirectional causal flow from the ecological footprint to energy use and economic growth, and from renewable energy innovations and energy consumption to economic growth. Therefore, the policy implications for this study, among others, include the provision of grants and subsidies for research in renewable energy to enhance sustainable environmental quality.
Keywords: CO2 emissions; energy use; financial development; renewable energy innovations; trade policy uncertainty; fi=Taloustiede|en=Economics|